Հայերեն նորակազմ բառերի իմաստաբանական քննության հարցեր - Գալստյան, Ա. Ս.
В статье рассматриваются особенности внутрисистемного и внеязыкого процесса образования новых слов в современном армянском языке. Для языко- вого обозначения новых понятий часто предлагаются несколько вариантов слов, из которых с течением времени выбираются и входят в основной словарный фонд языка те, которые соотвествуют нужным критериям. Анализируются процесс употребления вариантов слов օդորակիչ [odorakičc] “кондиционер”, հոգեկերտվածք [hogekertvackc] “менталитет”, ներզատաբան [nerzataban] “эндокринолог”, а также особенности образования новых слов тематической группы цветонаименований. The article deals with the peculiarities of the intrasystem and extra-linguistic process of formation of new words in the modern Armenian language. For the linguistic denotation of new concepts several variants of words are often proposed, from which over time those that meet the necessary criteria are selected and included in the acquisitive vocabulary of the language. The process of using the variants of the words օդորակիչ [odorakičc] "conditioner", հոգեկերտվածք [hogekertvackc] "mentality", ներզատաբան [nerzataban] "endocrinologist", as well as the features of formation of new words of thematic group of colornames are analyzed.
Keywords: Լեզվաբանություն